Knowledge sharing in is personnel: organizational behavior's perspective - Teh, P.L.; Yong, C.C. (INT Assoc Computer Info System, 2011)
This research investigates the roles of sense of self-worth, in-role behavior, and organizational citizenship behavior in supporting individuals' knowledge sharing behavior, by incorporating a motivational aspect into the theory of reasoned action. Structural equation modeling analysis of survey data from a group of 116 Information Systems personnel revealed that two variables (i.e., sense of self-worth and in-role behavior) are positively related to the attitude toward knowledge sharing. Both subjective norm and organizational citizenship behavior are independent and positively related to an intention to share knowledge, while the attitude toward knowledge sharing is negatively related to intention to share knowledge. Individuals' knowledge sharing behavior is predicted with more favorable intention to share knowledge. This research and its findings have implications for organizational administrators in Information Technology (IT) firms to enhance intrinsic motivation among employees, and develop better reciprocal relationships and interpersonal interactions of employees to facilitate successful knowledge sharing.